Family Involvement In Enhancing Self-Care Management Among Type 2 Diabetes Patients In A Rural Community: A Qualitative Case Study in a Rural Indonesian Setting - Anih Kurnia; Risna Silpiawati; Betty Suprapti (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2026)
ABSTRACT Type 2 Diabetes Mellitus (T2DM) is an increasing public health concern in Indonesia, particularly in rural areas with limited access to healthcare services. Successful diabetes management relies on consistent self-care behaviors, including adhering to medication, regulating diet, engaging in physical activity, and monitoring glucose levels. Family involvement plays a crucial role in supporting these behaviors; however, evidence from rural Indonesian contexts remains limited. This study aimed to describe how family involvement contributes to improving self-care management among patients with T2DM in a rural community. A qualitative case study was conducted with five families in Cigunung Village through semi-structured interviews, direct observations, and document reviews. Thematic analysis identified five major themes: family perceptions and responsibilities, emotional–instrumental–spiritual support, family strategies in assisting self-care, challenges encountered, and behavioral changes in patients. Family involvement enhanced medication adherence, dietary management, motivation, and emotional well-being despite socioeconomic barriers. These findings highlight the pivotal role of family support in effective diabetes management. Community nurses are encouraged to adopt family-centered and culturally sensitive approaches in health education and home-based empowerment programs to strengthen sustainable self-care practices.